Experimental and analytical investigation of impact dampers in free vibration reduction with coulomb friction. (March 2022) - Safaeifar, Hossein; Farshidianfar, Anooshirvan
The presence of vibration in structures and machines can establish failures and reduce the efficiency. Passive dampers have been used extensively for vibration control because of their simple concept. One of these dampers is impact damper (ID). Impact dampers are suitable to operate in harsh environments and effective over a wide range of frequencies. In this paper, the experimental and theoretical investigation on the effect of the ID in free vibration of a cantilever beam is done. The lateral motion of the free end of the cantilever beam is modeled as one degree of freedom (1-DOF) system. The motion of the 1-DOF system equipped with the ID with Coulomb friction is studied analytically. Free vibration of cantilever beam investigated experimentally. The experimental results are presented and discussed. The damping inclination of the ID in various experimental and theoretical studies is proposed. The results show the validation between the experimental and the theoretical studies.